1995
DOI: 10.1093/oxfordjournals.humrep.a135769
|View full text |Cite
|
Sign up to set email alerts
|

Placebo-controlled trial of treatment of unexplained secondary recurrent spontaneous abortions and recurrent late spontaneous abortions with i.v. immunoglobulin

Abstract: The aim of this trial was to investigate whether infusions of i.v. immunoglobulins (Ig) to women with secondary recurrent spontaneous abortions and recurrent second trimester spontaneous abortions can increase the rate of successful pregnancy. In a prospective, double-blind, placebo-controlled trial, infusions of i.v. Ig (Nordimmun) or placebo were given during pregnancy to 34 women with a history of either unexplained recurrent spontaneous abortion subsequent to a birth or including at least one second trimes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
86
1
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(89 citation statements)
references
References 0 publications
1
86
1
1
Order By: Relevance
“…Moffet et al (31) also argued that assays of the cytotoxic activity of blood NK cells in vitro had no Table II Negative Stephenson [39] (51) Stephenson [51] (4) German Grp [64] (52) None Christiansen [34] (53) Christiansen [58] (54) Perino [46] (55) Jablonowska [41] (56) meaning as the function of uterine NK cells in vivo was mediated by the cytokines they produce and not by cytotoxicity. However, there are many types of in vitro assays that do not measure functionally relevant activity in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Moffet et al (31) also argued that assays of the cytotoxic activity of blood NK cells in vitro had no Table II Negative Stephenson [39] (51) Stephenson [51] (4) German Grp [64] (52) None Christiansen [34] (53) Christiansen [58] (54) Perino [46] (55) Jablonowska [41] (56) meaning as the function of uterine NK cells in vivo was mediated by the cytokines they produce and not by cytotoxicity. However, there are many types of in vitro assays that do not measure functionally relevant activity in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the prevalence of a 14 base pair insertion in exon 8 of the HLA-G gene was found to be increased significantly in secondary RM patients, compared with controls. These studies provide evidence that particular HLA polymorphisms characterize secondary RM [5][6][7].Huge heterogeneity between eight randomized placebocontrolled trials of IVIg to patients with RM has been observed, with live birth rates in placebo groups ranging from 29 to 79% [8][9][10][11][12][13][14][15]. The differences in live birth rates observed between these studies raises questions as to whether the patient categories are the same.…”
mentioning
confidence: 99%
“…Huge heterogeneity between eight randomized placebocontrolled trials of IVIg to patients with RM has been observed, with live birth rates in placebo groups ranging from 29 to 79% [8][9][10][11][12][13][14][15]. The differences in live birth rates observed between these studies raises questions as to whether the patient categories are the same.…”
mentioning
confidence: 99%
“…The clinical guidelines on RPL stated by the Royal College of Obstetricians and Gynecologists [10], for example, have indicated lack of strong evidence for the use of immunotherapy. This conclusion was mainly drawn by Daya et al [11] and from the meta-analysis of six studies performed by the German RSA/IVIG Group [12], Christiansen et al [13], Stephenson et al [14], Perino et al [15], Coulam et al [16] and Kipron et al [17]. Five European pilot studies with a total of 172 patients as well as one controlled double-blind multicenter study including 64 patients were considered; using albumin as a placebo, a similar conclusion was drawn, i.e.…”
Section: Introductionmentioning
confidence: 96%